Gene expression profile predicts response to antitumor necrosis factor in children with Crohn's disease: A Porto group biobank study, and a systematic review - Atia, Ohad; Azulay, Asaf; Focht, Gili; Ledder, Oren; Lev-Tzion, Raffi; Schwerd, Tobias; Siebert, Kolja; Faro, Tim; Chapuy, Laurence; Groleau, Véronique; Grzywacz, Kelly; Amar, Soumaya; et al. (Journal of pediatric gastroenterology and nutrition, 2025)
OBJECTIVES: There is a paucity of validated predictors of response to anti-tumor necrosis factor (TNF) in pediatric Crohn's disease (CD). We aimed to evaluate the predictive utility of intestinal gene expression to predict response to anti-TNF in children with CD. METHODS: We enrolled children with CD before initiating anti-TNF as part of the prospective biobank of the pediatric inflammatory bowel disease Porto group of ESPGHAN. Genes potentially associated with therapeutic response were first preselected from a systematic literature review. Ribonucleic acid was extracted and sequenced from inflamed ileal biopsies of 20 children before initiating anti-TNF (13 with steroid-free remission [SFR] at 12 months, and seven with primary nonresponse [PNR]). An external validation cohort including 22 children (21 SFR, 1 PNR) was enrolled from Germany and Canada. Using maximum relevance-minimum redundancy (mRMR) methods, we constructed a support vector machine-learning model evaluated via leave-one-out cross-validation and permutation testing. RESULTS: Of 1799 studies identified in the systematic review, 24 met the inclusion criteria, reporting on 150 genes possibly associated with anti-TNF response in children or adults. In the Porto group cohort, 30 genes were associated with treatment response, of which five (TREM1, IL23R, CCL7, IL17F, and YES1) were most frequently selected. A multivariable model of these genes achieved high predictive utility (area under receiver operating characteristic curve: 0.88 [95% confidence interval: 0.69-1.0], sensitivity/specificity/positive predictive value/negative predictive value: 92%/71%/86%/83%). The same genomic signature in external validation achieved accuracy of 82% (i.e., 18/22 samples were classified correctly, including the single PNR patient). CONCLUSION: Increased expression of five genes is associated with higher rate of anti-TNF response in pediatric CD. Prospective studies are now warranted to validate these genes as biomarkers for treatment selection.
Keywords: inflammatory bowel disease; RNA expression; biologics